2013
DOI: 10.1186/1471-2202-14-41
|View full text |Cite
|
Sign up to set email alerts
|

Method parameters’ impact on mortality and variability in rat stroke experiments: a meta-analysis

Abstract: BackgroundEven though more than 600 stroke treatments have been shown effective in preclinical studies, clinically proven treatment alternatives for cerebral infarction remain scarce. Amongst the reasons for the discrepancy may be methodological shortcomings, such as high mortality and outcome variability, in the preclinical studies. A common approach in animal stroke experiments is that A) focal cerebral ischemia is inflicted, B) some type of treatment is administered and C) the infarct sizes are assessed. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 374 publications
1
62
0
Order By: Relevance
“…Our success rate of inducing an infarction by a 90-minute middle cerebral artery occlusion was 90 % (only one animal had no ischemic lesions according to the MRI examination), in accordance with another report (Bacigaluppi, tomi & Hermann, 2010). With reference to the animal models, the infarction size reportedly is dependent on rat strains: the Wistar strain and the intraluminal filament procedure, using a silicone-coated filament, gives the lowest variability (Strom et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our success rate of inducing an infarction by a 90-minute middle cerebral artery occlusion was 90 % (only one animal had no ischemic lesions according to the MRI examination), in accordance with another report (Bacigaluppi, tomi & Hermann, 2010). With reference to the animal models, the infarction size reportedly is dependent on rat strains: the Wistar strain and the intraluminal filament procedure, using a silicone-coated filament, gives the lowest variability (Strom et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse strain in Paper I, C57BL6, is the most widely used inbred strain (https://www.jax.org/strain/000664, accessed 2015-10-05) and was therefore considered suitable for a study with the goal of establishing a protocol for other researchers to adopt in their experiments. For Paper IV outbred albino Wistar rats were used, and this strain is very common in rat stroke experiments (second only to Sprague Dawley among the 304 studies included in Paper II [133]). We have previously worked with Sprague Dawley rats (another outbred albino strain) in our lab but switched to Wistar in an effort to try to reduce infarct size variability [133,134].…”
Section: Animalsmentioning
confidence: 99%
“…For Paper IV outbred albino Wistar rats were used, and this strain is very common in rat stroke experiments (second only to Sprague Dawley among the 304 studies included in Paper II [133]). We have previously worked with Sprague Dawley rats (another outbred albino strain) in our lab but switched to Wistar in an effort to try to reduce infarct size variability [133,134]. Both Papers I and IV have a bearing on the clinical issue of hormone replacement therapy for menopausal women, why female animal models were considered more relevant.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…By working on data from 502 control groups described in 346 articles, Ström et al have investigated the method parameters' impact on mortality and variability. Their metaanalysis has revealed that the Wistar strain and intraluminal filament procedure using a silicone-coated filament resulted in smallest infarct size variability (36).…”
Section: █ Discrepanciesmentioning
confidence: 99%